Conceptual Frameworks of Science, Technology and Innovation Policy - Benoit Godin (Foresight and STI Governance)
The paper looks at conceptual frameworks in science studies and science policy, and at the narratives involved. It is based on the work conducted over the last ten years on science policy and science statistics. The first section offers a brief tour d’horizon on the frameworks developed over the twentieth century and used among governments and the OECD. The second section looks at the rhetoric or narratives involved in the conceptual frameworks. This is followed by the third section on some features of the policy process specific to the OECD. The paper concludes with some thoughts on what ends a framework really serves.